Pengaruh Model Pembelajaran Learning Cycle 5E (Engagement, Exploration, Explanation, Elaboration, Evaluation) Terhadap Kemampuan Kognitif Siswa Kelas VIII Mata Pelajaran Fiqih MTs. Al-Washliyah P. Berandan - Yunita Sitinjak, Ahmad Fuadi, Usmaidar (Pusdikra Publishing, 2023)
The problems found at the research location were: The results of initial observations made by researchers at the research location, the researchers obtained information from the Jurisprudence teacher in class VIII who explained that the subject teacher still used conventional learning methods so that teaching and learning activities in class tended to be technical. giving lectures, giving assignments to students and asking questions so that the implementation of learning can be categorized as conventional or classical teaching activities. Based on the problems mentioned above, the researcher conducted research using quantitative methods to determine the significant relationship between variables x and variable y by using data collection techniques through questionnaires or questionnaires consisting of a number of questions. The results of this study are: After conducting in-depth research it turns out that there is an influence between the Learning Cycle 5 E Learning Model on the Cognitive Ability of Class VIII Students of MTs Al-Washliyah Private Pangkalan Brandan by knowing the proportion of the determination of the value of r xy is as follows: 0.471 x 100% = 47 .1%. Thus it can be understood that the Learning Cycle 5 E Learning Model has provided direction of 47.1% towards the formation of student personality.